Concentrado protéico de folhas de mandioca como complemento alimentar para tilápias do Nilo - Bohnenberger, Leandro (2008)
Although cassava leaves are rich in proteins, vitamins and minerals and are easily found at low prices, their direct consumption is limited due to the presence of anti-nutritious and/or toxic substances. Aiming to create alternatives to the use of these leaves, the present paper aimed to determine the coefficients of apparent digestibility (AD) from the dry matter (DM), crude protein (CP) and crude energy (CE) of cassava leaf protein concentrate (CLPC) for Nile Tilapia, and to evaluate its inclusion in Nile Tilapia food. The CLPC has been extracted through isoeletric precipitation, method described by CEREDA & VILPOUX (2003). In the CLPC, it has been determined the perceptual of crude protein (CP), ether extract (EE), ashes, dry matter (DM) and crude energy (CE), which have shown 48.42%, 13.57%, 3.48%, 93.01% and 5527 Kcal/kg., respectively. 24 tilapias with an average weight of 86.92 ± 36.70 g have been used. The animals have been submitted to fecal collection methodology, through sedimentation, in tanks with funneled shapes. The DM, CP, and CE of CLPC have presented AD of 33.06%, 66.57% and 30.06%, respectively, thus, showing digestible protein and energy values of 32.23% and 1661.13 kcal of DE/kg. In order to evaluate CLPC inclusion in Nile Tilapia food, 300 larvae at the age of 7 days old have been used, which were distributed in 20 aquariums with capacity for 30 liters of useful volume, in a fully randomized outline with five treatments and four repetitions, pointing out that the experimental unit is consisted of an aquarium with 15 tilapia larvae. Five isoproteic and isoenergetic diets have been elaborated containing 38.6% of digestible protein and 3300 kcal of DE/kg of diets with level of 0, 5, 10, 15 and 20% of CLPC inclusion. At the end of the experimental time, differences have not been noticed (W>0.05) on the final average weight, weight gain, final length and survival of larvae which were fed with diets containing CLPC. It is concluded that CLPC is a protean food and it may be used in diets for tilapia in initial phase in up to 20% of inclusion without causing performance and survival harms.